Causal analysis of PM2.5 propagation characteristics during the winters of 2015 to 2023 in Hubei Province, China - Yige Zheng; Shangbin Xiao; Hongen You; Yutong Liu (Scientific Reports)
Abstract To discuss the causes and characteristics of occasional severe winter pollution in Wuhan, Hubei Province, China amidst the continuous improvement of the atmospheric environment, this research utilizes air quality monitoring data from various cities in Hubei Province during the winters of 2015–2023, analyzing changes in air quality in Hubei Province using PM2.5 concentration values as an indicator. We employ the Convergent Cross Mapping (CCM) method, using Wuhan and other cities in Hubei Province as examples, to reveal the causal impact of other cities within Hubei Province on winter PM2.5 pollution in Wuhan from a causality perspective. The results indicate an improvement in air quality during the winters of 2015–2023 in Hubei Province. The PM2.5 concentration in Wuhan during winter is influenced by four other cities within Hubei Province, indicating a clear causal relationship between the PM2.5 concentrations in these two regions. The Convergent Cross Mapping (CCM) method accurately identifies both the strength and direction of the causal relationship between two variables, providing invaluable guidance for subsequent research in atmospheric environmental governance.